2017
DOI: 10.1088/1361-6455/aa8d81
|View full text |Cite
|
Sign up to set email alerts
|

Scattering theory of efficient quantum transport across finite networks

Abstract: We present a scattering theory for the efficient transmission of an excitation across a finite network with designed disorder. We show that the presence of randomly positioned networks sites allows to significantly accelerate the excitation transfer processes as compared to a dimer structure, if only the disordered Hamiltonians are constrained to be centrosymmetric, and to exhibit a dominant doublet in their spectrum. We identify the cause of this efficiency enhancement in the constructive interplay between di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…Hence, it is necessary to identify structural elements, which provide efficient quantum transport in the presence of disorder. It has been demonstrated that a specific symmetry in the Hamiltonian, called centrosymmetry, improves significantly the overall transport across the network [7][8][9][10]. Recently, these studies have been extended to interacting disordered networks, modeled by embedded Gaussian ensembles (EGEs) [11][12][13] and their centrosymmetric version (csEGEs) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is necessary to identify structural elements, which provide efficient quantum transport in the presence of disorder. It has been demonstrated that a specific symmetry in the Hamiltonian, called centrosymmetry, improves significantly the overall transport across the network [7][8][9][10]. Recently, these studies have been extended to interacting disordered networks, modeled by embedded Gaussian ensembles (EGEs) [11][12][13] and their centrosymmetric version (csEGEs) [14,15].…”
Section: Introductionmentioning
confidence: 99%